2006
DOI: 10.1037/0893-164x.20.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Use of warning messages to modify gambling beliefs and behavior in a laboratory investigation.

Abstract: This laboratory study assessed the effectiveness of warning messages intended to aid in the control of gambling. Participants were 120 undergraduate students from an urban state university who reported previous gambling activity. They were recruited to play a computerized roulette game with imaginary money. Money left at the end of play was exchanged for raffle tickets for a prize drawing. Participants were randomly assigned to 1 of 2 conditions. In the warning-message condition, participants received an educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 22 publications
6
51
1
1
Order By: Relevance
“…Importantly, players also indicated that pop-up messages would have a greater effect than static messages if displayed on real EGMs. These results are consistent with previous research findings that pop-up messages are associated with reductions in session length and potentially decreased gambling expenditure (Floyd et al, 2006;Ladouceur & Sevigny, 2003) and importantly extend previous findings by demonstrating an impact on actual gambling behaviour, which supports the implementation of pop-up messages as an effective mechanism to facilitate responsible gambling.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Importantly, players also indicated that pop-up messages would have a greater effect than static messages if displayed on real EGMs. These results are consistent with previous research findings that pop-up messages are associated with reductions in session length and potentially decreased gambling expenditure (Floyd et al, 2006;Ladouceur & Sevigny, 2003) and importantly extend previous findings by demonstrating an impact on actual gambling behaviour, which supports the implementation of pop-up messages as an effective mechanism to facilitate responsible gambling.…”
Section: Discussionsupporting
confidence: 82%
“…Similar to previous empirical laboratory studies (Cloutier et al, 2006;Floyd et al, 2006;Ladouceur & Sevigny, 2003) pop-up messages appear to be superior to static signs in enhancing message recall and influencing thoughts. However, this study advances the knowledge base by demonstrating the impact of pop-up messages on within-session thoughts and behaviors, and predicted future gambling behavior with a both young adult regular EGM players and more representative sample of regular EGM gamblers.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In relation to message content, the limited literature available suggests that gambling signage should contain information highlighting harms associated with gambling, including potential addictiveness, rectifying erroneous gambling-related cognitions and providing correct odds and probabilities, so that the individual is able to make an informed choice (Blaszczynski et al, 2004;Steenbergh et al, 2004;Schrans et al, 2004;Blaszczynski et al, 2005;Floyd et al, 2006;Monaghan and Blaszczynski, 2007). It is important to highlight that a recent review of the effectiveness of existing responsible gambling research found signage on EGMs to have limited value (Williams et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the successes of these methods, there is evidence to suggest that briefer cognitive interventions may be effective in reducing anxiety and fears relating to negative evaluations in social phobia, reducing the frequency and believability of negative cognitions in specific phobias, and increasing restraint and ability to manage food cravings [21] [25] found that the provision of information explaining probability resulted in increased resistance to gambling fallacies; however, this increased resistance did not translate in reducing gambling behaviour. On the other hand, Floyd, Whelan and Meyers [23] found that individuals who received a brief educational intervention prior to gambling along with brief messages addressing irrational gambling beliefs whilst gambling, reported fewer irrational beliefs and took fewer risks whilst engaging in gambling activities. It is possible that the laboratory setting and presence of a researcher mayreduce the external validity of the findings.…”
Section: Brief Cognitive Interventions For Disordered Gamblingmentioning
confidence: 99%